2010
DOI: 10.3109/14659890903013059
|View full text |Cite
|
Sign up to set email alerts
|

Whole team training to reduce burn-out amongst staff on an in-patient alcohol ward

Abstract: In 2005 the alcohol in-patient ward at South London and Maudsley NHS Foundation Trust participated in a 2-day training programme designed to reduce levels of burn-out amongst staff. The training intervention was derived from a large-scale project that focused on in-patient and community mental health staff in five European countries. A research component was built into the work, with levels of staff burn-out being measured prior to the training intervention and 1 month afterwards, using the Maslach Burn-out In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
11
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 12 publications
1
11
0
Order By: Relevance
“…Emotional exhaustion is defined as being over-extended and exhausted by one’s work (Hill et al, 2010) [ 16 ]. Hill and colleagues (2010) [ 16 ] conducted a study on the faculty of an inpatient alcohol dependence facility and found that, before training, staff reported, on average, elevated levels of emotional exhaustion, suggesting that, collectively, the team was highly emotionally exhausted. After the training, MBI emotional exhaustion scores were down slightly, but not to a significant degree.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Emotional exhaustion is defined as being over-extended and exhausted by one’s work (Hill et al, 2010) [ 16 ]. Hill and colleagues (2010) [ 16 ] conducted a study on the faculty of an inpatient alcohol dependence facility and found that, before training, staff reported, on average, elevated levels of emotional exhaustion, suggesting that, collectively, the team was highly emotionally exhausted. After the training, MBI emotional exhaustion scores were down slightly, but not to a significant degree.…”
Section: Resultsmentioning
confidence: 99%
“…Depersonalization refers to an unfeeling and impersonal response to clients (Hill et al, 2010) [ 16 ]. Over half of the participants in the study conducted by Hill and colleagues (2010) [ 16 ] were classified in the high range for depersonalization on the MBI prior to training. The psychoeducational training resulted in a decrease of depersonalization scores, but not to a significant degree.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is well-accepted that the characteristics of the individuals participating in the training (e.g., extraversion) as well as the characteristics of the teams or organisations in which these individuals work (e.g., team cohesion) have been shown to affect training transfer (Blume et al, 2010;Burke & Hutchins, 2007;Cheng & Ho, 1999;Colquitt et al, 2000). However, many studies fail to take either the trainees' individual characteristics (Clarke, 2002;Hill et al, 2010;Velasco & Harder, 2014) or the influence of their team and work environment into account (Castillo-Gualda et al, 2019;Salas et al, 2008;Skodova & Lajciakova, 2013). Such studies are important for identifying which specific trainee or team characteristics influence training transfer, but do not enable a comparison between these two domains.…”
Section: Introductionmentioning
confidence: 99%
“…Robert et al conducted a training program on coping with burnout for the staff of alcohol inpatient ward and used Maslach Burnout Inventory for evaluating the staff afterward 13 .…”
mentioning
confidence: 99%